Petrogeochemistry of Amphibolites from Shivpura District Bhilwara, Rajasthan, India - Thomas, Harel; Paudel, Lalu (Journal of Institute of Science and Technology, 2015)
Amphibolites are frequently observed in the medium- to high-grade metamorphic rocks of Shivpura. These amphibolites are the result of the metamorphism of pre-existing mafic igneous rocks under medium to high grade P-T conditions and consist essentially of hornblende–plagioclase–garnet–clinopyroxene-epidote–iron oxide. Geochemically, these orthoamphibolites are tholeiitic, show association with non-orogenic environment and shift to subalkaline derivatives with progressive differentiation. It is also clear that the parent magma for these rocks was highly evolved in nature. Paper records the petrography, geochemical characters and a probable origin of these amphibolites. Journal of Institute of Science and Technology, 2015, 20(2): 103-112